Landsdommerkorpset under adelsvælden REKRUTTERING, KARRIEREMØNSTRE OG STATUS - Ladewig Petersen, E. (Historisk Tidsskrift, 1993)
The article discusses the office of landsdommer (provincial judge) during the Sixteenth and Seventeenth centuries. Based on accessible sources the patterns of recruitment and the careers of the holders of office are etablished. The article concludes, that the office is stabilized after 1536, that officeholders came from the lower echelons of the nobility, and that the office was neither prestigious nor well paid. During and after the critical years of the 158os a certain aristocratization of the office took place, and also a professionalization - at least compared to the first part of the century. The governnment seems to have stressed the need for academic education in view of the growing demands of the office. The landsdommer seems to have been recruited from the lower strata of the nobility compared to the offices of lensmand or rigsråd, and chances of promotion remained small until the 16405. Yet the office of landsdommer may have worked as a vehicle for economic and social mobility. From an institutional point of view the most important development is the institutionalization and bureaucratization of the office during the Seventeenth century, comparable with the development of other offices. Still, compared with Sweden these processes were less significant in Denmark.